Vascular plant one-zinc-finger protein 2 is localized both to the nucleus and stress granules under heat stress in Arabidopsis. (4th March 2017) - Koguchi, Misaki; Yamasaki, Kanako; Hirano, Tomoko; Sato, Masa H.
ABSTRACT: VASCULAR PLANT ONE-ZINC FINGER (VOZ)1/and VOZ2 have an ability to bind to the specific cis -element in the AVP1 promoter of Arabidopsis, which function on the PhyB-dependent flowering and possibly in various stress responses as potential transcription factors, although nuclear localization of VOZ proteins is still unclear. In this study, we found that VOZ2 is dispersed throughout the cytoplasm under normal growth conditions, whereas VOZ2 is transferred not only to the nucleus but also to the cytoplasmic foci under heat stress conditions. The VOZ2 foci predominantly co-localized with a marker of stress granules (SGs), which were cytoplasmic granular structures for mRNA storage and decay under abiotic stress conditions. We also demonstrated that GFP-VOZ2 with a nuclear localization signal was rapidly degraded via the ubiquitin/proteasome pathway under the heat stress conditions. Also, stress-related expression of DREB2A in the voz1voz2 mutant was significantly upregulated by heat stress as compared with that in the wild-type Arabidopsis . Our results suggest that VOZ2 is localized to SGs and nucleus under heat stress conditions, and functions as a transcriptional repressor of DREB2A in Arabidopsis .